Unconventional magnonic surface and interface states in layered ferromagnets - Khalil Zakeri (Nature Portfolio, 2021)
Magnons are the quantized spin waves, which describe the collective magnetic excitations and the long-range magnetic order in a solid. Here, the authors describe how to engineer magnonic band structures at the interface and surface of ferromagnetic layered structures and how such magnonic states alter the transport properties.